Hubungan Antara Kecerdasan Emosional dan Kecerdasan Spiritual dengan Perilaku Keagamaan pada Siswa - Lestariningsih, Ika Tri; Purwanto, Purwanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between emotional intelligence and spiritual intelligence on religious behavior, as well as emotional intelligence and spiritual intelligence together on religious behavior in MTs students in Jumantono District, Karanganyar Regency for the 2020/2021 academic year. The research method used is the correlational method. The population in this study were all students of class VIII as many as 194 students. The sample is some of the Madrasah students in Jumantono District as many as 130 students. The results showed: 1) there was a positive and significant relationship between emotional intelligence and religious behavior because the results obtained a significance value of 0.002 < 0.05; and the value of rX1Y is 0.269 > r table = 0.1779. 2) there is a positive and significant relationship between spiritual intelligence and religious behavior because the results obtained a significance value of 0.002 < 0.05; and the value of rX2Y is 0.268 > r table = 0.1779. 3) there is a positive and significant relationship between emotional intelligence and spiritual intelligence variables together with religious behavior with a significance level of 0.002 <0.05. The contribution of emotional intelligence and spiritual intelligence to religious behavior is 7.5%. The relationship between emotional intelligence and spiritual intelligence together with religious behavior is shown by the regression line equation = 64.266 + 0.183X1 + 0.170X2. In conclusion, there is a positive and significant relationship between each variable, namely emotional intelligence and spiritual intelligence on religious behavior and jointly emotional intelligence and spiritual intelligence are related to religious behavior. Key words: emotional intelligence, spiritual intelligence, religious behavior